2015
DOI: 10.1097/eja.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in glottic visualisation by using the C-MAC PM video laryngoscope as a first-line device for out-of-hospital emergency tracheal intubation

Abstract: Use of the C-MAC PM video laryngoscope is associated with improved visualisation of the glottis according to the Cormack and Lehane grading system and an excellent success rate for out-of-hospital tracheal intubation. These results suggest that the use of C-MAC PM as a first-line device for tracheal intubation by out-of-hospital emergency medical services is a safe procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
4
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 35 publications
5
49
4
7
Order By: Relevance
“…Retrospective analysis of video footage demonstrated that body fluids (blood, vomitus, or secretions) obstructing the view of the airway was negatively associated (OR = 0.29; p = 0.01) with C‐MAC intubation success. In another prehospital study, Hossfeld and colleagues evaluated the use of the C‐MAC as a first‐line device in 228 patients intubated by helicopter emergency medical service physicians. Similar to our findings, they noted a high incidence of patients with a blood or vomitus contaminated airway (29.4%), but despite this a very low incidence of lens contamination (0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analysis of video footage demonstrated that body fluids (blood, vomitus, or secretions) obstructing the view of the airway was negatively associated (OR = 0.29; p = 0.01) with C‐MAC intubation success. In another prehospital study, Hossfeld and colleagues evaluated the use of the C‐MAC as a first‐line device in 228 patients intubated by helicopter emergency medical service physicians. Similar to our findings, they noted a high incidence of patients with a blood or vomitus contaminated airway (29.4%), but despite this a very low incidence of lens contamination (0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Having established that rapid sequence induction is indispensable in obstetric general anaesthesia, the question is whether direct laryngoscopy or videolaryngoscopy should be preferred during emergency caesarean section in a patient with anticipated difficult intubation. A robust line of evidence suggests that videolaryngoscopy is highly beneficial in a variety of settings ; because of enhanced glottic visualisation, videolaryngoscopy has a 93% success rate at the first intubation attempt in non‐obstetric patients, an overall failure rate of 1%, and functions as an effective rescue device even after failed awake fibreoptic intubation . Krom et al use a pessimistic model to predict failure of videolaryngoscopy.…”
Section: The Case For Videolaryngoscopes In Obstetric Anaesthesiamentioning
confidence: 99%
“…In the prehospital setting, helicopter emergency medical service (HEMS) physicians successfully managed failed direct laryngoscopy with the GlideScope (Verathon) (14) or the video laryngoscope (C-Mac, Karl Storz, Tuttlingen, Germany) (15,16). However, randomized prehospital control trials addressing video laryngoscopy versus direct laryngoscopy are spare and limited to a single study in cardiac arrest patients.…”
mentioning
confidence: 99%